Mütareke döneminde Rum nüfus hareketleri (1918-1922) - Mutlu, Cengiz (My University, 2011)
Rumlar, yüzlerce yıl Türklerin egemenliğinde barış içerisinde geleneklerine, kültürlerine ve dinlerine dokunulmaksızın yaşamışlardı. Gerek batılı devletlerin desteği gerekse milliyetçilik akımının tesiriyle 1821’de Mora’da ayaklanma başlatan Rumlar 1830’da devletlerini kurmuşlardı. Balkan Savaşları sırasında Yunanistan’a destek veren Osmanlı Rumlarının bir kısmı, firar ederek Yunan Ordusu saflarında savaşmıştı. Savaş sırasında bazı Rumların isyanı, asırlarca beraber yaşadıkları Müslümanlara yaptıkları zulümler, beraber yaşama fikrinin sorgulanmasına ve mübadele konusunun gündeme gelmesine sebep olmuştu . 1914 yılı başında Osmanlı Devleti ile Yunanistan arasında nüfus mübadele sözleşmesi yapılmış ise de çıkan savaş buna mani olmuştur. Savaş sırasında özellikle kıyı kesimlerdeki Rumların İtilaf Devletleri’ne casusluk yapması, çeteler kurarak köylere saldırması Osmanlı Devleti’ni önlemler almak zorunda bırakmıştı. Mondros Mütarekesi ile geri dönen Rumların asayişi bozucu bazı hareketleri görüldüğü gibi, uygunsuz davranışları da görülmüştür. Mütareke döneminde binlerce Rum’u Türkiye’ye göç ettirerek nüfus çoğunluğu sağlamak isteyen Yunanistan diğer taraftan Avrupa ve Amerika’da yaptığı propaganda ile Türkiye’yi köşeye sıkıştırmaya çalışmıştı. Karadeniz sahillerinde casusluğun artması, Pontusçu çetelerin Müslüman köylerine saldırılarını yoğunlaştırması ve Yunan donanmasının çıkarma yapma ihtimalinin artması üzerine Ankara Hükümeti sahildeki Rumları içeriye alma kararı almıştı. Batı cephesinde de benzer gerekçelerle bir kısım Rum’u dahile sevk eden Ankara Hükümeti, diğer taraftan karşı propagandaya girişmiştir. Büyük Taarruzla birlikte başlayan Yunan bozgununun akisleri Anadolu’nun her tarafında yankılanmıştı. Kaçan Yunan askerleri yanlarında Rumları da götürmüştür. Böylece Rumlar batılıların vaatlerine kanmaları dolayısıyla doğup büyüdükleri toprakları terk etmek zorunda kalmışlardır. Bu çalışmada mütareke dönemi olan 1918-1922 arasındaki Rum nüfus hareketleri incelenmiştir.

The Greeks under the Turkish rule had lived in peace and prosperity, and maintained their culture, religion and language without any Turkish intervention for centuries. Not only because of nationalism influence of the French Revolution but also due to interference of Western great powers, the Greeks had mutinied against the Ottoman Empire in 1821 in the Morea and they found their own state in 1830 after the Treaty of Adrianople concluded by the Ottoman Empire and the Russian Empire. During the Balkan Wars between 1912 and 1913, many Ottoman Greeks had supported Greece and fought against the Ottomans by deserting the Ottoman land. Due to Greeks’ fierce cruelty against the Turks and that Muslims that lived in peace with Christians for ages, issue of population exchange was started to be thought. Although, at the beginning of 1914, the Ottoman Empire and Greece had signed a truce regarding population exchange, because of World War One, this exchange was not completed. In the course of WWI, since the Greeks, especially living in the Ottoman coasts, found bandits, invaded the Muslim villages, and worked as fifth column of the Allies, the Ottoman Empire had to take hard safety measures against them. After the Armistice of Moudros between the Ottomans and the Allies in 1918 in order to conclude WWI, many Greeks, left their old home before, returned back the Ottoman territory and began to ruin public order. During the armistice period, Greece had wanted to chance population density in their favor by migrating Greeks to the Ottoman land, and Greece had tried to press the Ottoman Empire by implementing great propaganda in the Western public opinion. Because of increasing espionage in Black sea region, attacks of Pontus Greeks against innocent Muslims and possible deployment of Greek Naval Army, the Ankara Government made an important decision to migrate Greeks from coastal regions to inner part of Turkey. Due to similar reasons, many Greeks were migrated from Western Front. Meanwhile, the Ankara government started to increase its propaganda and use mass media in order to handle negative publicity of enemies. After the Great Offensive of Turks, Greece was decisively defeated by General Mustafa Kemal and the Greeks had to flee from Turkey. While escaping, the Greek Army brought many Greeks behind them to Greece because of Turkish reprisals. Therefore, they had to desert their home land due to Western promises for them. In this dissertation, Greek Population Movements between 1918 and 1922 during the Armistice Period was examined.
Keywords: Göçler_Rumlar; Göçler_Tarih; Nüfus Değişimi